Premeditated Murder and Violent Theft Against A Journalist In Pangkalpinang: A Rational Choice Theory Perspective - M. Adha Al Kodri; Muazri Rizky Mufti; Muhammad Husen; Izzah Septella; Muhammad Zubdat Sabilal Mutadin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze premeditated murder and violent theft against a journalist in Pangkalpinang through the perspective of rational choice theory. The research uses a qualitative method with a case study design. Data were collected through unstructured interviews, field observation, and document review related to the chronology of the case, the relationship between the offender and the victim, the crime location, and post-crime actions. The findings show that the crime was not a spontaneous act, but a sequence of criminal decisions involving motive, access, opportunity, location selection, violence, and efforts to reduce risk after the offense. The work relationship between the offender and the victim became an important factor because it provided social access, information, and an opportunity to approach the victim. The plantation area also increased the opportunity for crime because it had limited social supervision. From the perspective of rational choice theory, the offender is understood as an actor who assessed benefits, risks, and obstacles through bounded rationality. This study offers a theoretical contribution to criminological studies, especially in explaining serious crime through the concept of bounded rationality. Practically, this study highlights the importance of protecting local journalists, strengthening situational awareness, and developing community-based security systems.